The revolt of the provinces : anti-Gypsyism and right-wing politics in Hungary - Szombati, Kristóf (Berghahn Books, 2018)
"The first in-depth ethnographic monograph on the New Right in Central and Eastern Europe, The Revolt of the Provinces explores the making of right-wing hegemony in Hungary over the last decade. It explains the spread of racist sensibilities in depressed rural areas, shows how activists, intellectuals and politicians took advantage of popular racism to empower right-wing agendas and examines the new ruling party's success in stabilizing an 'illiberal regime'. To illuminate these important dynamics, the author proposes an innovative relational framework, focusing on interaction between social antagonisms emerging on the local level and struggles waged within the political public sphere"-- Provided by publisher.
Keywords: Racism -- Hungary.; Romanies -- Hungary -- Social conditions.; Nationalism -- Hungary.; Right-wing extremists -- Hungary.; Hungary -- Politics and government -- 21st century.; Racisme -- Hongrie.; Tsiganes -- Hongrie -- Conditions sociales.; Nationalisme -- Hongrie.; Extrémistes de droite -- Hongrie.; Hongrie -- Politique et gouvernement -- 21e siècle.; HISTORY -- Europe -- Western.; HISTORY -- Europe -- Germany.; POLITICAL SCIENCE / General; Romanies -- Social conditions; Right-wing extremists; Racism; Nationalism; Conservatism; Democracy; Politics and government; Right and left (Political science); Hungary; 2000-2099; Since 1989